Homeotic genes in Drosophila's bithorax complex - The legacy of Ed Lewis - Karch, Francois (Henry Stewart Talks, 2018)
Segmentation in Drosophila, Homeotic mutations, Developmental genetics, Ed Lewis, Bithorax mutations, Enhancer trapping, Hox gene clusters